NATIONAL-CULTURAL CHARACTERISTICS OF PHRASEOLOGICAL UNITS IN GERMAN LANGUAGE AND TRANSFER OF THEIR SYNONYMS IN UZBEK LANGUAGE (Scientific journal of the Fergana State University, 2023)
In this article, the national-cultural characteristics of phraseological units in the German language are mentioned. Proper understanding of the meaning of phrases is very important, especially in artistic translation. The article was written with the aim of allowing not only German language teachers, but also the general public who are directly interested in the history of culture, its semantic aspects, to compare these aspects with the corresponding analogues of their native language. Therefore, the article explains the logical content of phraseologisms with the help of relatively simplified phraseologisms, as well as synonymic phraseologisms of some words and phrases in the Uzbek and German languages